Identification of active compounds and antifungal activity of Toona sinensis leaves fractions against wood rot fungi - RIZKI RABECA ELFIRTA; SYAMSUL FALAH; DIMAS ANDRIANTO; TIEN LASTINI (Biodiversitas Journal of Biological Diversity, 2018)
Elfirta RR, Falah S, Andrianto D, Lastini T. 2018. Identification of active compounds and antifungal activity of Toona sinensis leaves fractions against wood rot fungi. Biodiversitas 19: 1313-1318. Inhibitory activities of surian or toon (Toona sinensis) leaves fraction origin Sumedang, West Java, Indonesia against wood rot fungi (Ganoderma boninense IPBCC 10.658, Trametes versicolor InaCC F200, and Phanerochaete chrysosporium IPBCC 93.259) were studied. The samples were macerated using methanol and acetone. The results of brine shrimp lethality test (BSLT) showed that the methanol extract had the highest cytotoxicity of LC50 at 29.76 ?g/mL and inhibit the growth of G. boninense (27.78%), T. versicolor (79.26%) and P. chrysosporium (81.11%). The methanol extract was then subsequently fractionated using n-hexane, diethyl ether, and ethyl acetate respectively. The diethyl ether fraction was found to have the highest inhibitory activity against T. versicolor (46.30%) and P. chrysosporium (81.11%). This fraction was further separated using column chromatography and analyzed using thin layer chromatography (TLC), which gave six fractions. Antifungal test exhibited that fraction 5 had the highest antifungal properties against T. versicolor (74.07%) and P. chrysosporium (80.37%). Inhibition of P. chrysosporium resulted in abnormal growth of hyphae morphology as indicated by changes in its growth direction and excessive hyphae branching. Additionally, the results of LC-MS/MS experiment indicated toon leaves fraction 5 which contains N-[2- (D-Glucopyranosyloxy)ethyl]-2-hydroxy-N-[2hydroxy3 (octadecyloxy) propyl] butanamide dan Brucine compounds that were regarded as the antifungal compounds.